Contimporanul. (Bucuresti : Institutul de Arte Grafice Eminescu, 1922)
Contimporanul (antiquated spelling of the Romanian word for "the Contemporary", singular masculine form) was a Romanian (initially a weekly and later a monthly) avant-garde literary and art magazine, published in Bucharest between June 1922 and 1932. Edited by Ion Vinea, Contimporanul was prolific in the area of art criticism, dedicating entire issues to modern art phenomena, and organizing the Bucharest International Modern Art Exhibit in December 1924 (with the participation of Constantin Brâncuși).Several writers contributing to Contimporanul soon moved on to adopt more specific styles, including a literary form of constructivism (which was the dominant style of the magazine for a certain period),[1] Dada, and, eventually, surrealism.(https://en.wikipedia.org/wiki/Contimporanul)
Fotokopies+CD-ROM
Online: Beinecke Digital Collections: https://brbl-dl.library.yale.edu/vufind/Record/3542537
Roemeens
Tijdschriften
Keywords: constructivisme; avant-garde.; futurisme